2017
DOI: 10.1002/dev.21518
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ejection period reactivity to reward is associated with anhedonic symptoms of depression among adolescents

Abstract: Pre-ejection period (PEP) reactivity to reward has been posited as a specific index of behavioral approach and incentive motivation, suggesting it might be uniquely associated with the affective and motivational deficits of anhedonia. This study evaluated PEP reactivity to a reward task as a predictor of depressive symptoms among adolescents, examining global depressive symptoms as well as specific anhedonic and nonanhedonic symptoms clusters. Participants included 76 adolescents, ages 11–15 years (52% female)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…Hence, a reduction or absence of heart rate and ventricular contractility increases might indicate a subconscious reduction or absence of psychological task engagement or motivation to engage in the motivated performance situation, despite unchanged conscious self-reports of motivation. This explanation is also consistent with the association between blunted CVR and depression, as depression features anhedonia, a core symptom characterized by reduced sensitivity to and reduced anticipatory motivation to pursue rewards (Ahles et al, 2017;Franzen & Brinkmann, 2016;Treadway & Zald, 2013).…”
Section: Potential Explanations For Blunted Cvr To Stresssupporting
confidence: 84%
“…Hence, a reduction or absence of heart rate and ventricular contractility increases might indicate a subconscious reduction or absence of psychological task engagement or motivation to engage in the motivated performance situation, despite unchanged conscious self-reports of motivation. This explanation is also consistent with the association between blunted CVR and depression, as depression features anhedonia, a core symptom characterized by reduced sensitivity to and reduced anticipatory motivation to pursue rewards (Ahles et al, 2017;Franzen & Brinkmann, 2016;Treadway & Zald, 2013).…”
Section: Potential Explanations For Blunted Cvr To Stresssupporting
confidence: 84%
“…When difficulty is uncertain, people’s effort level reflects the importance of the incentive—people’s effort is proportional to how much they value the goal. Many studies have used uncertain-difficulty paradigms to study how depressive symptoms affect effort (e.g., Ahles, Mezulis, & Crowell, 2017; Brinkmann & Franzen, 2013, 2017; Franzen & Brinkmann, 2016a, 2016b), including one study with a clinical sample (Franzen, Brinkmann, Gendolla, & Sentissi, 2018). When the performance standard is unclear, dysphoric and depressed participants expend less effort, suggesting that the incentives are less valuable.…”
mentioning
confidence: 99%
“…Reward responsivity refers to the degree to which an individual experiences positive response to reward and has been conceptualized as a distinct trait-like tendency to experience reward that is part of the larger behavioral approach system (Carver & White, 1994). For example, empirical evidence has shown associations between PEP reactivity to a myriad of reward-related processes, including behavioral approach toward incentives (Ahles et al, 2017;Beauchaine et al, 2001;Brenner et al, 2005), and self-reported trait reward responsiveness (Franzen et al, 2019). It is posited that these associations may be driven at least in part given PEP as a peripheral marker of mesolimbic dopamine reactivity to reward processing and reinforcement (Beauchaine & Gatzke-Kopp, 2012;Berridge, 2007;Forbes & Dahl, 2012).…”
Section: Maternal Autonomic Nervous System Regulation and Parentingmentioning
confidence: 99%